NOX1/NADPH oxidase regulates the expression of multidrug resistance‐associated protein 1 and maintains intracellular glutathione levels. (6th February 2019) - Wen, Xiaopeng; Iwata, Kazumi; Ikuta, Keiko; Zhang, Xueqing; Zhu, Kai; Ibi, Masakazu; Matsumoto, Misaki; Asaoka, Nozomi; Liu, Junjie; Katsuyama, Masato; Yabe‐Nishimura, Chihiro
Abstract : The involvement of superoxide‐generating NADPH oxidase (NOX) in the cytotoxic effects of cigarette smoke extracts has been documented. However, the underlying molecular mechanisms and NOX isoform involved have not been fully clarified. Among the different NADPH oxidase isoforms identified so far, NOX1 and NOX4 were found to be expressed in rat H9c2 cardiomyocytes. When H9c2 cells were exposed to acrolein or methyl vinyl ketone (MVK), major toxic components of cigarette smoke extracts, a dose‐dependent decline in cell viability was observed. Unexpectedly, disruption of Nox1 as well as Nox4 significantly exacerbated cytotoxicity induced by acrolein or MVK. Compared with Nox4 ‐disrupted cells, Nox1 ‐disrupted cells were more vulnerable to acrolein and MVK at lower concentrations. Disruption of Nox1 markedly attenuated the levels of total and reduced glutathione (GSH) in H9c2 clones. Reduction in the cystine level in the culture medium to deplete intracellular GSH significantly exacerbated acrolein or MVK‐induced cytotoxicity. Nox1 disruption neither attenuated the level of glutamate–cystine antiporter protein nor the activity of glutamate–cysteine ligase, both rate‐limiting factors for GSH synthesis. On the other hand, increased expression of multidrug resistance‐associated protein 1 (MRP1), which mediates glutathione efflux, was demonstrated in Nox1 ‐disrupted cells. The augmented toxicity of acrolein and MVK in these cells was partially but significantly blunted in the presence of an MRP1 inhibitor, reversan. Taken together, these results show that NOX1/NADPH oxidase regulates the expression of MRP1 to maintain intracellular GSH levels in cardiomyocytes and protect against cytotoxic components of cigarette smoke extracts. A novel crosstalk between NOX1 and MRP1 was demonstrated in this study. Abstract : Cytotoxicity induced by acrolein and methyl vinyl ketone, major toxic components of cigarette smoke extracts, was significantly exacerbated in H9c2 cardiomyoblasts by disruption of Nox1, one of the superoxide‐generating NADPH oxidase isoforms. Disruption of Nox1 markedly attenuated intracellular glutathione levels and was associated with increased expression of multidrug resistance‐associated protein 1 (MRP1). A novel crosstalk between NOX1 and MRP1 was demonstrated in this study.